LEADERSHIP AND STUDENT UNIONISM, CHALLENGES AND SOLUTIONS IN THE NIGERIAN TERTIARY EDUCATION SYSTEM (COLLEGES OF EDUCATION, POLYTECHNICS AND UNIVERSITIES) - Peter, Zuokemefa Enebraye; Ebimobowei, Sese Tuperekiye (European Scientific Journal, ESJ, 2015)
Student Union leadership is formed to promote and defend the welfare needs of the Students’ Community in Nigerian Tertiary Education System. Union leaders engage Government through dialogue on certain policies and the authorities of institutions to provide certain minimum services that will promote a sustained environment for academic interactions. This includes teaching, learning, social and research activities. Student Union Government (SUG) serves as the voice of the Students in all Tertiary Institutions in Nigeria. The Authorities through the Students’ Union Government is able to instill discipline and know the feelings and request of the Students. This view is corroborated by Longing (2003) and Ekekwem (2006). Most often, the refusal of Government and Management of institutions to address the legitimate needs of Students’ Union leaders leads to conflicts which manifest in demonstrations and unrest with severe consequences. This article examines an ideal student’s unionism, its responsibilities, causes of protest and challenges in Union leadership and provides suggested solutions to mitigate unrest by administrators of tertiary institutions and government.